PRACTICAL ASPECTS OF THE FORMATION OF YOUTH CIVIL POSITION IN THE PEDAGOGICAL PROCESS - Jurs, Pāvels; Samuseviča, Alīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Emphasizing the social value of the democratic state and civic society, the authors of the publication have updated the theoretical nuances of attitudes towards citizenship of young people as well as the formation of civic position and empirical findings in the field of civic engagement and promotion opportunities. The objective of publication is: basing on the theoretical understanding of the dimensions of the citizenship formation, to characterize the manifestations of civic attitudes of 9th grade students in the pedagogical process and to assess the practical aspects of the formation of civic position through approbation of upbringing and educational program in ensuring young people's civic engagement.